Cervical Spinal Cord Compression in Adult Scoliosis - Nakashima, Hiroaki; Kawakami, Noriaki; Ohara, Tetsuya; Saito, Toshiki; Tauchi, Ryoji; Imagama, Shiro (Global spine journal, 2023)
Study Design Retrospective cohort study. Objectives The aim was to examine cervical spinal cord compression (SCC) in adult scoliosis and clarify the prevalence of and risk factors for cervical SCC. Methods This study included 270 adult scoliosis patients and 1211 healthy volunteers. Cervical SCC was evaluated on cervical magnetic resonance imaging (MRI). The rates of SCC for those with adult scoliosis and the healthy volunteers were compared. Logistic regression analysis was conducted to examine the factors associated with cervical SCC on MRI. Results In cases with adult scoliosis, preoperative major scoliosis curve was 56.0° ± 18.8°, and cervical SCC was detected in 25 patients (9.3%). Among the healthy volunteers, 64 cases with cervical SCC were detected. Only in cases with adult scoliosis, logistic regression analysis revealed higher age (OR 1.09, 95% CI 1.04–1.14, P < .001), narrow canal diameter (OR 2.27, 95% CI 1.35–3.85, P = .002), and inferior sagittal balance (OR 2.45, 95% CI 1.02–5.89, P = .04) as significant risk factors. In the logistic regression analysis in all subjects (including adult scoliosis and healthy volunteers), higher age (OR 1.08, 95% CI 1.06–1.10, P < .001) and narrow canal diameter (OR 1.62, 95% CI 1.37–1.92, P < .001) were also found to be significant risk factors, but the presence of scoliosis was not a significant factor. Conclusions Adult scoliosis itself was not significantly associated with cervical SCC. Inferior sagittal balance in addition to scoliosis constituted a significant risk factor for cervical SCC.